Hubungan Kehamilan Remaja Terhadap Kejadian Prematuritas dan Kemampuan Perawatan Bayi Baru Lahir di Desa Wonorejo - Devi Amelia Putri; Tutik Rahayu; Sri Wahyuni (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Teenage pregnancy is important issue because reproductive organs are not ready and can endanger mother and child she is carrying. Other impacts are premature babies and increased maternal and child mortality rates, due to lack of proper newborn care. was determine relationship between teenage pregnancy and incidence of prematurity and ability to care for newborns. This research is a type of quantitative research using a Cross Sectional approach. Data collection was carried out using questiobbaire. Number of respondents was 70 people with a purposive sampling technique. Based on analysis result, it was obtained that from 70 respondents of study, majority had characteristics of adolescence as much 64,3%. Overall gender characteristics were female 100%, with characteristics of majority of education level having a high school education of 57,1%. Characteristics of majority of jobs were housewives as much 45,7% and private employees as much 42,9%. Result of study also showed that teenage pregnancy less than 19 years old experienced premature births 28% and mature 72%, while teenage pregnancy more than 19 years old experienced premature births 4,4% and mature 95,6%. Teenage pregnancy less than 19 years old were able to carry out newborn baby care with 48% good ability, 40% moderate ability, and 12% poor ability, while teenage pregnancy more than 19 years old were able to carry out newborn baby care with 77,1% good ability, 4,4% moderate ability, and 2,2% poor ability. Research result it can be concluded there is relationship between teenage pregnancy and incidence of prematurity and ability to care for newborns with p-value of 0,008 (<0,05) for incidence of prematurity and p-value of 0,000 (<0,05) for newborn care.